Women of Power: The Image of the Witch and Feminist Movements in Poland - Anczyk, Adam; Malita-Król, Joanna (Pomegranate, 2018)
The following article deals with the socio-political image of witches and concentrates on the links between certain witch images and the ideology of some feminist movements in contemporary Poland. The core stereotype of the witch (the dangerous yet very much needed Other in the Christian culture) is first presented, followed by its feminist interpretation (the free, independent woman who lives on the edge of patriarchal culture) and Pagan witch stereotype (which largely agrees with feminist interpretation). In the due course the brief history of intertwining web between modern witchcraft, women’s spirituality and feminism is shown, along with the examples of Margaret A. Murray, Z Budapest and Starhawk. The second part of the article is dedicated to the Polish background: from the feminist-political discourse to the image of the witch in the contemporary arts. Some recent cases – including organizing the First Official Rally of the 21st century Witches as the proclamation of tolerance and the social discussion on the statue of Katarzyna W?odyczkowa, the witch of Czelad? – are presented to show how the image of the witch has been incorporated to the broader feminist discourse, proving that the power of a female witch-figure remains a strong symbol and a core concept.